Canine Olfactory Detection - Otto, Cynthia M.; Marie Guest, Claire (Frontiers Media SA, 2020)
The olfactory ability of the dog far exceeds that of humans. In order to better understand how dogs interact with their world of scent, an understanding of the genetics, physics, physiology, neurobiology and behavioral applications of canine olfaction is essential. The application of canine olfaction to real world problems may provide new ways to look at diseases, disasters and other challenging problems that defy the other senses and technology. A critical evaluation of how dogs detect odors will increase the acceptance of these approaches. It is imperative that the value of dogs is objectively assessed and their potential capabilities are optimized through the development of learning theory and human-canine communication. Comparisons between dogs and other sensing approaches may serve to enhance the understanding and success of all forms of olfactory sensing. The dog remains the quintessential biological detector, through science addressing all aspects of olfactory based detection, we can enhance and augment that performance.